Working for Long Hours Is Associated With Dietary Fiber Insufficiency - Min, Jeehee; Lee, Dong-Wook; Kang, Mo-Yeol; Myong, Jun-Pyo; Kim, Hyoung-Ryoul; Lee, Jongin (Frontiers in Nutrition, 2022)
It has been suggested that long working hours are associated with various diseases through dietary patterns. However, few studies have reported the association between working hours and dietary habits. Thus, the objective of this cross-sectional study was to explore the difference in dietary fiber intake by working hours. Data of a total of 10,760 workers in South Korea who participated in the Korea National Health and Nutrition Survey (KNHANES), a nation-wide survey, were analyzed to determine different distributions of dietary fiber insufficiency using multiple logistic regression models. Fiber insufficiency proportion was different from working hour groups. 70.1% of the total population eat fiber insufficiently. Working <40 h group showed 66.8% of fiber insufficiency. But working more than 52 h group marked 73.2% of fiber insufficiency. Logistic regression analysis of 10,760 nation-wide study participants revealed that working for 41–52 h a week (OR: 1.32, 95% CI: 1.18–1.47) and working for over 52 h a week (OR: 1.42, 95% CI: 1.25–1.62) were significantly associated with insufficient fiber intake compared to workers with standard working hours (30–40 h a week). These associations were still robust in an adjusted model, with working for 41–52 h a week (OR: 1.13, 95% CI: 1.01–1.27) and working for over 52 h (OR: 1.26, 95% CI: 1.09–1.45) showing high associations with dietary fiber insufficiency. Those with long working hours tend to have insufficient intake of dietary fiber. To promote desirable dietary habits, intervention programs on working conditions should be considered.